1999
DOI: 10.1001/archotol.125.7.729
|View full text |Cite
|
Sign up to set email alerts
|

Life and Death in Otolaryngology

Abstract: Apoptosis is now understood to be important in the normal development and survival of all multicellular organisms. Deregulation of this normally tightly controlled process underlies a variety of disease states, including neoplasia, autoimmune disease, and disorders of the central nervous system. A better understanding of this process and its regulation may help otolaryngologists better understand diseases relevant to this specialty and will lead to improved therapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 106 publications
(120 reference statements)
1
0
0
Order By: Relevance
“…The decreased broblastic activity was caused by inadequate development of the brous layer and resulted in sclerosis of the brous layer. 8 In the present study we found also that the cells staining positively for Bcl-2 protein expression, stimulated broblastic proliferation and mast cell activity and were more obvious in group A (selenium treated) than group B (control).…”
Section: Discussionsupporting
confidence: 73%
“…The decreased broblastic activity was caused by inadequate development of the brous layer and resulted in sclerosis of the brous layer. 8 In the present study we found also that the cells staining positively for Bcl-2 protein expression, stimulated broblastic proliferation and mast cell activity and were more obvious in group A (selenium treated) than group B (control).…”
Section: Discussionsupporting
confidence: 73%